Polyindole and polypyrrole as a sustainable platform for environmental remediation and sensor applications. Issue 7 (2nd March 2022) - Thadathil, Anjitha; Pradeep, Hareesh; Joshy, Deepak; Ismail, Yahya A.; Periyat, Pradeepan
Abstract : This review focuses on the synthesis and improvement of two types of N-containing conducting polymers – polypyrrole and polyindole – as well as an in-depth analysis of their binary and ternary nanocomposites in the treatment of contaminants, sensing, and green chemistry. Abstract : Conducting polymer (CPs), which are Nobel Prize-winning materials, have opened an exciting area of research due to their substantial electrical conductivity, unique structures, and ability to generate new composite materials, and have wide applications ranging from optoelectronics to material science. Research on conducting polymers has triggered much attention in nanoparticle-incorporated composites, which provide enhanced synergistic properties even at low filler concentration, resulting in high-level performance in important fields such as chemistry and material science. This review focuses on the synthesis of nanocomposites of two main types of N-containing conducting polymers, namely, polypyrrole (PPY) and polyindole (PIN), as well as an in-depth analysis of their binary and ternary nanocomposites in the treatment of contaminants, sensing, and green chemistry. This review also covers different strategies for the versatile property improvement of these conducting polymers with unique applications. This review is expected to be useful for the field of chemistry to explore the possibility of new composite mixtures of conducting polymers in environmental and sensing applications.